The role of the modern informatics systems in assisted decisions - DRAGOMIR, Robert Gabriel (Annals of Spiru Haret University. Economic Series, 2016)
The present paper speaks about the complexity of the decisional phenomenon. First of all, we referred to the challenges of the informal society; strategic management is the one that occupies by them. Then we noticed that the most modern informational instruments are used by the strategic management in order to gain the best analysis and results. After that, we made references to the following solution of business intelligence: data warehouse, data cube OLAP and data mining. We presented their characteristics, advantages and disadvantages of usage one or another. In the end, we draw at the conclusions: the society has good premises of development by using such instruments.